Intrabreed variability and relationships for 41 carcass and meat traits in Pirenaica cattle - Panea, B.; Albertí, P.; Olleta, J.L.; Campo, M.M.; Ripoll, G.; Altarriba, J.; Sañudo Astiz, C. (Spanish Journal of Agricultural Research, 2008)
A total of 125 13-month-old, entire males of the Pirenaica breed were selected from among the progeny of nine different sires. They were used to study the intrabreed variability of 41 carcass and meat traits, including weights, lengths, diameters and perimeters, grading parameters, dissection of the sixth rib, pH, colour and meat texture variables, and sensory attributes. Pearson correlations were also calculated. Coefficients of variation ranged from 3.5% for dressing percentage to 47.0% for fat red index, and all of the values could be considered within the normal range for cattle. Carcass traits showed lower variability (11.7% on average) than meat variables (14.8% on average). Hence, to achieve a standardised product, it would be desirable to include in the breeding selection programme a variable that could be measured on the carcass and that can predict meat quality. Nevertheless, from the results of the present study, none of the variables studied fulfil this requirement, and further studies would be necessary to widen our knowledge on this subject.